Social Support Systems for the Elderly: A Comparative Study of Family and Institutional Care Models - Nurul Aisyah; Hendra Saputra (International Journal of Social Science and Humanity, 2024)
This study compares family-based and institutional care models for the elderly, focusing on their impacts on well-being and quality of life. Through interviews with elderly individuals and caregivers, the research assesses how each model meets the emotional, social, and healthcare needs of the elderly. Findings suggest that while family care offers emotional benefits, institutional models can provide better healthcare, calling for integrated approaches to eldercare.